Clinicopathologic features of renal cell carcinomas seen at the Aga Khan University Hospital in Kenya - Mutuiri, Anderson; Gakinya, Samuel (Frontiers in Medicine, 2022)
Introduction: Kidney cancer accounted for 1.8% of global deaths from cancer according to Globocan 2020 estimates with most of these cancers being renal cell carcinomas. Lower rates of renal cell carcinoma are reported for Africa and these are expected to change. The clinical and morphologic characteristics of renal cell carcinoma seen within Kenya have not been described before. This study aims to partially fill this gap. Materials and Methods: This was a cross-sectional descriptive study examining electronic histopathology reports from the Aga Khan University Hospital Nairobi Laboratory for the period January 2016 to May 2022 Results: Sixty cases of renal cell carcinoma were identified. The mean age at diagnosis was 55.3 years. The most common histologic subtype diagnosed was clear cell renal cell carcinoma (41.7%), followed by papillary renal cell carcinoma and renal cell carcinoma not further specified (both 21.7%) and chromophobe renal cell carcinoma (11.7%). The most frequent specimen was resections, followed by cores of renal masses. The mean tumor size was 8.5cm. Sixty-seven percent of patients presented with Stage 3 and above. Discussion: Renal masses were the commonest clinical indication for biopsy among the records reviewed. The male to female ratio as well as the mean age at presentation were comparable to what is described in literature for other regions of the world. The proportions of the commonest histologic subtypes matched what is described in other parts of the world. Challenges in the identification of histologic subtypes included having a limited panel of antibodies for diagnosis and the lack of genetic molecular tests for histotyping. Conclusion: The spectrum of histologic subtypes of renal cell carcinoma seen at a tertial referral hospital in Nairobi Kenya was similar to that described in other parts of Africa and the globe. The age at presentation with renal cell carcinoma was consistent with what has been described in literature. Challenges were identified in the accurate histotyping of renal cell carcinoma due to constrained resources. Majority of cases diagnosed presented at advanced stage.